Utilization of 4‐(trifluoromethyl)benzenesulfonates as Counter Ions Tunes the Initiator Efficiency of Sophisticated Initiators for the Preparation of Well‐Defined poly(2‐oxazoline)s. Issue 12 (10th April 2019) - Engel, Nora; Dirauf, Michael; Seupel, Susanne; Leiske, Meike N.; Schubert, Stephanie; Schubert, Ulrich S.
Abstract: During the last decades, poly(2‐oxazoline)s (POx) have gained increased interest due to their versatility. In particular, cationic ring‐opening polymerization (CROP) enables the synthesis of well‐defined polymers bearing quantitative α‐ and ω‐functionalities. In contrast to small initiating groups, the introduction of more sophisticated, respectively demanding groups remains challenging. To fulfill this challenge, the initiator should comply with one major requirement in order to yield well‐defined polymers: a fast and complete initiation. The straight forward two‐step synthesis of a novel initiator containing a 4‐(trifluoromethyl)benzenesulfonate (fluorylate, TosCF3 ) counter‐ion is herein presented to accomplish the introduction of a sophisticated functional 3‐(2‐(2‐ethoxy)ethoxy)ethoxy)prop‐1‐ene (TEG) initiating group. Kinetic studies are conducted in acetonitrile and chlorobenzene using the hydrophilic 2‐ethyl‐2‐oxazoline (EtOx) as well as the hydrophobic 2‐octyl‐2‐oxazoline (OctOx) as monomers to examine the influences of the solvent as well as the different monomers. In particular, the initiator efficiency is determined by 1 H and 19 F nuclear magnetic resonance spectroscopy and compared to the corresponding tosylate (TEGTos) and triflate (TEGTf). It is shown that the fluorylate combines the stability of the tosylate and an enhanced propagation rate comparable to the triflate. Abstract : The introduction of a sterically demanding α‐functionality by the aid of an initiator remains challenging for cationic ring‐opening polymerization (CROP). A new initiator containing a 4‐(trifluoromethyl)benzenesulfonate (fluorylate) as leaving group leads to a significant improvement. Therefore, kinetic studies are conducted in acetonitrile and chlorobenzene using 2‐ethyl‐2‐oxazoline (EtOx) as well as 2‐octyl‐2‐oxazoline (OctOx) and examined by 1 H and 19 F nuclear magnetic resonance spectroscopy.